2000
DOI: 10.1111/j.1749-6632.2000.tb06318.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction, Hemodynamic Forces, and Atherogenesisa

Abstract: Phenotypic modulation of endothelium to a dysfunctional state contributes to the pathogenesis of cardiovascular diseases such as atherosclerosis. The localization of atherosclerotic lesions to arterial geometries associated with disturbed flow patterns suggests an important role for local hemodynamic forces in atherogenesis. There is increasing evidence that the vascular endothelium, which is directly exposed to various fluid mechanical forces generated by pulsatile blood flow, can discriminate among these sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
469
0
9

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 760 publications
(499 citation statements)
references
References 41 publications
7
469
0
9
Order By: Relevance
“…Hinds et al found a similar increased adhesion of U-937 cells to the proximal part of the constriction in their idealized E-selectin coated axisymmetric stenosis (49). Taken together, our results and previous studies suggest that there is more firm attachment of leukocytes to an endothelium in the presence of complex shear gradients (31)(32)(33).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Hinds et al found a similar increased adhesion of U-937 cells to the proximal part of the constriction in their idealized E-selectin coated axisymmetric stenosis (49). Taken together, our results and previous studies suggest that there is more firm attachment of leukocytes to an endothelium in the presence of complex shear gradients (31)(32)(33).…”
Section: Discussionsupporting
confidence: 86%
“…Most of our understanding of leukocyte adhesion and endothelial cell dysfunction has come from parallel plate and rotational viscometer cell culture experiments (31,32). These studies have demonstrated that leukocyte attachment is dependent on the magnitude of the hydrodynamic forces, the contact frequency and duration, and the cellular response to shear stress (29,(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Indications that mechanical stimulation of cells, and endothelium in particular, is able to change some of their functions at biochemical and molecular level are reported in the literature [5]. In spite of the evidence that cells are sensitive to mechanical stimuli, the molecular mechanisms by which individual cells recognize and respond to external forces are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cells are the true player of the angiogenesis process. Several cardiovascular pathologies are caused by endothelial dysfunction (myocardial ischemia, atherosclerosis), thus growth factors and strategies able to restore the integrity of the endothelium and to promote angiogenesis can be viewed as innovative therapeutic approaches [3,4].Indications that mechanical stimulation of cells, and endothelium in particular, is able to change some of their functions at biochemical and molecular level are reported in the literature [5]. In spite of the evidence that cells are sensitive to mechanical stimuli, the molecular mechanisms by which individual cells recognize and respond to external forces are not well understood.…”
mentioning
confidence: 99%
“…Una característica común de la disfunción endotelial es la disminución de la biodisponibilidad de NO a nivel vascular (56), acompañada de otras alteraciones en el fenotipo endotelial que aumentan aún más la propensión a la vasoconstricción (57), trombosis, inflamación y a la proliferación celular en el lecho vascular (58)(59)(60)(61). La disfunción endotelial es el resultado de la presencia de FRCV y el desarrollo de aterosclerosis (62).…”
Section: Disfunción Endotelialunclassified